(NuKRA)QÇNSXKA LÆTERATURA (B:s)E (NP)QÆDRU^NIK DLQ (B11 (NKLASU ZAGALXNOOSWÆTNÆH NAW^ALXNIH ZAKLADÆW (B/s)E - (NsEMEN@K(B, (Ng(B. (Nf(B.,s; (NtKA^UK(B, (Ns(B.s; (NkOWALX^UK(B, (No(B.s ((NkI)QÇW (B:s)E (NoSW)QÆTA(B,s)E, 2006)
(NkNIGA PRISWQ^ENA L)QÆTERATURNOMU PROCESOWÆ W uKRAÇNÆ hh ST(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NuKRA)QÇNSXKA LÆTERATURAs)E -- 11 (NKLASs; (No(B. (NwI[NQs; (N`(B. (NqNOWSXKIJs; (Nl(B. (NkOSTEKOs; (Nm(B. (NsTELXMAHs; (Nw(B. (NsTUSs; (Nu(B. (NsAM^UKs; (Nm(B. (NhWILXOWIJs; (Nw(B. (NbARKA(B.s